Hubungan Antara Kebijakan Kepala Sekolah dan Peningkatan Kinerja Guru di SMA Negeri 4 Kabupaten Bantaeng - Muhammad Afdal (Jurnal Pendidikan Dirgantara, 2025)
This study examines (1). How to Implement Principals' policies in improving teacher performance in SMAN 4 Bantaeng, Bantaeng Regency. (2) How are the principal's policy measures in improving teacher performance at SMAN 4 Bantaeng, Bantaeng Regency. This type of research is a qualitative descriptive study, with the research location in SMAN 4 Bantaeng, Pallantikang sub-district Bantaeng sub-district, Bantaeng Regency. Determination of informants in this study was carried out using purposive sampling technique, where the selection was made intentionally based on predetermined criteria and based on research objectives. Data collection methods are by observation, interview, documentation. The data analysis method uses three stages namely, data reduction, data presentation and conclusion drawing / verification. The results of the research The implementation of the principal's policy in improving teacher performance in SMAN 4 Ban taeng. namely: 1) Holding professional coaching. 2) Holding Teacher Meetings (3). Improve teacher discipline. The steps taken by the school principal are: (1) the initial meeting of the teacher's school year, (2) facilitating the teacher to continue their studies (3) making a decision letter (SK) and (4) meeting coordinator for each field. (5) Guidance is guiding.